Dynamic Vegetation Simulations of the Mid‐Holocene Green Sahara. Issue 16 (28th August 2018) - Lu, Zhengyao; Miller, Paul A.; Zhang, Qiong; Zhang, Qiang; Wårlind, David; Nieradzik, Lars; Sjolte, Jesper; Smith, Benjamin
Abstract: The "Green Sahara" is a period when North Africa was characterized by vegetation cover and wetlands. To qualitatively identify the orbital‐climatic causation of the Green Sahara regime, we performed dynamic vegetation model (LPJ‐GUESS) simulations, driven by climate forcings from coupled general circulation model (EC‐Earth) simulations for the mid‐Holocene, in which the vegetation is prescribed to be either modern desert or artificially vegetated with a reduced dust load. LPJ‐GUESS simulates a vegetated Sahara covered by both herbaceous and woody vegetation types consistent with proxy reconstructions only in the latter scenario. Sensitivity experiments identify interactions required to capture the northward extension of vegetation. Increased precipitation is the main driver of the vegetation extent changes, and the temperature anomalies determine the plant functional types mainly through altered fire disturbance. Furthermore, the simulated vegetation composition also depends on the correct representation of soil texture in a humid environment like Green Sahara. Plain Language Summary: The Sahara Desert experienced wet and vegetated conditions in the past. The vegetation‐atmosphere feedbacks play an important role in sustaining vegetation cover in that region. Here we perform dynamic vegetation model simulations to reproduce herbaceous and woody vegetation types in North Africa 6, 000 years ago. We further investigate separately the relative importance of various climate forcings (precipitation, temperature, radiation, and soil temperature) in inducing the "Green Sahara." We conclude that vegetation extent is mainly determined by precipitation, while vegetation composition is mainly determined by temperature, and the correct representation of soil texture is also important. Future modeling work considering dynamic vegetation‐atmosphere feedbacks could be valuable for providing analogues to Sahara/Sahel climate and vegetation regimes in the past and future. Key Points: A dynamic vegetation model reproduces the Green Sahara vegetation regime during the mid‐Holocene as suggested by proxy data The mid‐Holocene precipitation anomalies determine the vegetation extent, while temperature anomalies determine the vegetation composition Dynamic representations of fire impact and soil texture are important prerequisites for modeling Green Sahara conditions